2005
DOI: 10.1021/jm049191x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Comparative in Vitro Cytotoxicity Studies of Platinum(II), Palladium(II), and Gold(III) Methylsarcosinedithiocarbamate Complexes

Abstract: This work reports on the synthesis, characterization, and in vitro cytotoxic activity of some new platinum(II), palladium(II), and gold(III) derivatives of methylsarcosinedithiocarbamate and its S-methyl ester, to study their behavior as potential antitumor agents. The biological activity of these compounds, as determined by growth inhibition and apoptosis induction, has been investigated in both human leukemic promyelocites HL60 and human squamous cervical adenocarcinoma HeLa cell lines, and their activity ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
88
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(92 citation statements)
references
References 40 publications
(72 reference statements)
2
88
0
2
Order By: Relevance
“…Therefore, selection of suitable ligands to enhance the stability is a big challenge in the design of gold(III) complexes. The Au(III) ion is best coordinated by at least two chelating nitrogen donors which lower the reduction potential of metal center and thereby stabilize the complex (Giovagnini et al 2005;Che et al 2003;Casini et al 2008). The stability of the complexes facilitated extensive pharmacological investigations, both in vitro and in vivo (Tieking 2008;Casini et al 2008Casini et al , 2009Ortiz et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, selection of suitable ligands to enhance the stability is a big challenge in the design of gold(III) complexes. The Au(III) ion is best coordinated by at least two chelating nitrogen donors which lower the reduction potential of metal center and thereby stabilize the complex (Giovagnini et al 2005;Che et al 2003;Casini et al 2008). The stability of the complexes facilitated extensive pharmacological investigations, both in vitro and in vivo (Tieking 2008;Casini et al 2008Casini et al , 2009Ortiz et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, the efficacy of platinum drugs is badly affected by systemic toxicities and drug resistance, and the pharmacokinetics of most platinum drugs is largely unknown [1,2,3]. In recent years, platinum complexes with bioactive molecules, natural compounds, targeting groups or nonmaterial's has been interested by chemical and biomedical researchers [4,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Gold compounds have been found to display promising antitumor activities [4]. For cytotoxicity or antitumour activities, a wide variety of gold(III) complexes were studied [9,10] and some of them even retain efficacy against the cisplatin-resistant cell lines [11,12]. Several research groups reported the antitumor activity of gold compounds, which indicates the remarkable interaction of gold ions with biomolecules [13].…”
Section: Introductionmentioning
confidence: 99%